Down range : a transitioning veteran's career guide to life's next phase - Murphy, James D. (James Daniel), 1964-; Duke, William M. (Wiley, 2014)
Military veterans prepare for the next mission in their careers Written by veterans who have successfully made the transition, Down Range offers career planning guidance to U.S. military veterans coming off active duty. This is NOT simply a guide to transitioning from the military to the civilian world. This is NOT a guide to getting a job. This book IS a guide to developing a post-military career, not just for the first few days, weeks, or months after active duty, but for the rest of your employed life. This simple and effective planning process has been taught to more than 1 million busine.